Biogeography : an ecological and evolutionary approach - Cox, C. Barry (Christopher Barry), 1931-; Moore, Peter D. (Hoboken, NJ : Wiley, 2010)
'Biologists searching for a resource that explores all of the exciting changes that have occurred recently in the field will turn to this eighth edition. It offers insight into the multidisciplinary nature of the field, presenting a sound historical base, up-to-date coverage, and a look at the latest controversies. The authors evaluate conflicting theories and provide a reasoned judgment as to which is preferable. In a new chapter the authors examine marine biogeography, so that biologists can compare and analyze the data, patterns and problems arising from continental, marine and island biogeography'--
Buku bacaan asas fakulti.
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Biogeography -- Textbooks